Management Of Dusung Negeri Waai District Of Salahutu, Central Maluku District - Realdi Rupilu; Junianita. F Sopamena; Raihana Kaplale (Cita konsultindo, 2023)
This study aims to determine the management of traditional Dusung agroforestry as a model of land and forest use in Maluku, especially by the people of Negeri Waai District, providing economic, ecological and socio-cultural benefits that are still being maintained today. In looking at the factors that influence hamlet management, economic factors include income and social factors, including education level. Hamlet management from an economic aspect, namely the number of commodities produced can increase family income and reduce the risk of crop failure. So that the needs of food and clothing and community boards can be met and can meet the educational needs of children to a higher level.